Pelatihan Pemanfaatan Platform Ecommerce Sebagai Upaya Peningkatan Kinerja Dan Keberlangsunagan Bisnis Dimasa Pandemi (Studi Kasus: UMKM Di Medan) - Merry Moy Mita (Jurnal Pemberdayaan Masyarakat, 2024)
The emergence of Covid-19 has had many effects felt by various business groups, one of which is MSMEs. The condition of MSMEs after the Covid-19 pandemic struck is very worrying, limited access and policies increasingly mean that MSMEs do not have the opportunity to survive, let alone develop their business. The aim of this community service activity is to provide knowledge and understanding to MSMEs in the city of Medan to start using the e-commerce platform as a new sales medium amidst limited interaction. The method used in this community service is the lecture method and giving 3 interaction sessions in this activity. The result of this service is that the knowledge and skills of business actors in Medan City regarding e-commerce platforms are increasing, as demonstrated by the enthusiasm of the training participants